Evaluación del efecto antimicrobiano de los aceites esenciales de orégano y canela en el pan integral - Rubio Peralta, María Belén (2017)
This graduation project aims to evaluate the antimicrobial effect of oregano and cinnamon essential oils in wholemeal bread, as a natural alternative to the substitution of chemical conservatives, which, nowadays are used in the bakery industry, and according to studies have shown secondary effects in consumers’ health. For this purpose, wholemeal bread batches were made and natural conservatives were incorporated in different dose and application. After this, for the microbiological analysis deep sowings were made in SDA + chloramphenicol midst, including witness samples and samples containing a chemical conservative, in order to compare results. Sowings were incubated at 30 oC for 21 days, in which, microbiological growth was controlled, as well as pieces of bread were kept in polyethylene in a dry place and ambience temperature and the percentage of samples spoilage were quantified. As a result, it was obtained that mass applications of both essential oils delay fungus growth that are main responsible of bread spoilage (Penicillium and Aspergillus) longer in comparison with sodium benzoate; being cinnamon essential oil the one that shows better results for extended time. In order to know the new additives acceptability, surveys were made to assess flavor mainly. Wholemeal bread was made with each essential oils minimal concentrations and people tasted the samples. Results show that 67% of them liked the flavor and 93% are willing to consume bread with essential oils. Economically, the use of essential oils turns into an increase of production costs, reaching triple of the value. But the benefit of this application consist in extend shelf life and therefore the time the product can be in hanger, decreasing losses for product expiration.